2016
DOI: 10.4168/aair.2016.8.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Using Periostin as a Biomarker in the Treatment of Asthma

Abstract: Periostin acts both as an extracellular matrix protein belonging to the fasciclin family and as a matricellular protein functioning in cell activation by binding to its receptors on the cell surface. It has been established that periostin is a downstream molecule of interleukin (IL)-13, a signature type 2 cytokine, and that periostin plays an important role in the pathogenesis of allergic diseases, including asthma. Based on these findings, much attention has been paid to periostin as a biomarker useful in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 60 publications
(90 reference statements)
3
80
0
3
Order By: Relevance
“…lebrikizumab (anti-IL-13 antibody) [13]. This final feature is also supported by the results of studies which demonstrated a higher efficiency of lebrikizumab therapy in asthmatic patients with increased periostin serum level, compared to patients with a low level of serum periostin [32,33].…”
Section: Periostin and Bronchial Asthmasupporting
confidence: 73%
See 2 more Smart Citations
“…lebrikizumab (anti-IL-13 antibody) [13]. This final feature is also supported by the results of studies which demonstrated a higher efficiency of lebrikizumab therapy in asthmatic patients with increased periostin serum level, compared to patients with a low level of serum periostin [32,33].…”
Section: Periostin and Bronchial Asthmasupporting
confidence: 73%
“…Thus, an increased periostin level associated with eosinophilia and Th2 mediated inflammation is seen in a specific type of bronchial asthma. Activated Th2 cells are able to produce several inflammatory cytokines, such as IL-4 and IL-13, as the main activators of periostin gene expression in the bronchial wall in asthmatic disease [13,19].…”
Section: Periostin and Bronchial Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Periostin is a protein that acts as an extracellular and matricellular matrix protein and its production is induced by IL-13 and IL-4 which are both cytokines that figure prominently in Th2 inflammation. 57 Immunohistochemical studies have identified periostin deposition on the basement membrane of individuals with asthma, suggesting that it contributes to sub-epithelial fibrosis in asthma. 57 Periostin does not appear to be as a useful biomarker in childhood asthma because periostin levels are high normally in growing children such that differences between healthy children and those with asthma is comparatively small or not significant.…”
Section: ) Serum Total Igementioning
confidence: 99%
“…57 Immunohistochemical studies have identified periostin deposition on the basement membrane of individuals with asthma, suggesting that it contributes to sub-epithelial fibrosis in asthma. 57 Periostin does not appear to be as a useful biomarker in childhood asthma because periostin levels are high normally in growing children such that differences between healthy children and those with asthma is comparatively small or not significant. 58 Although it might be a useful biomarker of response to drugs that might be commercialized in the future, there is currently no clinically available commercial assay for periostin.…”
Section: ) Serum Total Igementioning
confidence: 99%